The Effect of Motivation, Work Discipline, and Work Environment on Employee Job Satisfaction at Platinum Hotel & Convention Hall Balikpapan - Tony, Nur Luthfiyyah; Arrywibowo, Imam; Marlindawaty, Marlindawaty (Journal Research of Social Science, Economics, and Management, 2026)
The hospitality industry in Balikpapan is experiencing significant growth due to the development of the Nusantara Capital City (IKN), leading to intense competition among four-star hotels. Platinum Hotel & Convention Hall Balikpapan faces challenges in maintaining service quality and employee performance, making job satisfaction a crucial factor in organizational success. Job satisfaction is influenced by various factors, including motivation, work discipline, and the work environment. This study aims to analyze the influence of motivation, work discipline, and work environment on employee job satisfaction at Platinum Hotel & Convention Hall Balikpapan. This study uses a quantitative approach with a survey method. Data were obtained through the distribution of questionnaires to 98 employees who were designated as research samples, with the selection criteria being employees who had worked for more than two years. The data analysis method used is Partial Least Squares (PLS), with the help of SmartPLS software. The results of the study show that motivation has a positive and significant effect on employee job satisfaction. Work discipline also has a positive and significant effect on employee job satisfaction. In addition, the work environment has a positive and significant effect on employee job satisfaction. These findings indicate that increasing work motivation, applying work discipline consistently, and creating a conducive work environment can improve employee job satisfaction at Platinum Hotel & Convention Hall Balikpapan.